Comparative study of the agricultural sector in Romania and the main member states of the U.E. - Ionuț Laurențiu Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
To identify the problems faced by the Romanian agricultural sector and to identify viable development solutions, a comparative analysis of the competitiveness of the Romanian sector with the other member states of the European Union is necessary. In this regard, in the present research, a quantitative analysis of the statistical data taken from the Eurostat databases was performed, to determine the competitiveness of the sector compared to other Member States. The main technical-economic indicators from the last statistical publication (structural survey) from 2016 were analyzed. Following the determination of the positioning of Romanian agriculture, recommendations and solutions can be identified to develop it and increase competitiveness.
Keywords: Q01; Q10; 330; Romanian agriculture; competitiveness; vegetable sector; comparative study